Strategic Management of Scout Extracurricular Activities to Enhance Holistic Character Development in Primary School Students - Rini Martini; Ahmad Sukandar (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study investigates the management of Scout extracurricular activities in elementary schools as a strategy to counter declining student discipline, particularly amidst the growing influence of digital technology. Utilizing a qualitative case study approach, the research was conducted at SDN Tegallame and SDN Mulyasari, analyzing the implementation of Scout programs through G.R. Terry's Planning, Organizing, Actuating, and Controlling framework. Data were collected via participatory observation, in-depth interviews with principals, Scout coordinators, instructors, and students, and document analysis, subsequently analyzed using the Miles and Huberman model. Findings reveal that systematic POAC management of Scout activities effectively fosters discipline, responsibility, independence, and leadership. Meticulous planning, involving student input, structures both routine and incidental experiential learning events. Clear organizing through a hierarchical structure with instructors as multifaceted mentors and students as patrol leaders cultivates responsibility and group management. Actuating emphasizes practical habituation, such as punctual attendance and task division, reinforced by comprehensive evaluation and reward systems to internalize Pancasila Student Profile values. Despite challenges in human resources, infrastructure, and funding, schools demonstrated adaptability through instructor training, stakeholder collaboration, facility optimization, and alternative funding, ensuring program sustainability. Evaluation consistently showed measurable improvements in student discipline and participation, including achievements in Scout competitions. This research addresses a critical gap by focusing on the management of Scout activities as a specific strategy for discipline improvement, especially in the context of digital-era challenges. The study's novelty lies in articulating a systematic, measurable, and adaptive Scout management model that integrates habituation, role modeling, task assignment, and continuous evaluation, offering a replicable template for educational institutions seeking to cultivate disciplined, resilient, and responsible students.